Archer's Compound Interest and Annuity Tables - James, A. C. (London: Shaw &Sons ltd., 1974)
This edition shows considerable departures from all previous editions, both in the range of values of the variables and the manner of display. The very comprehensive range of interest rates presented necessitates three volumes (this being vol. 1) to cover all annual rates at intervals of one sixteenth per cent.
Originally compiled by Archer, J. A.
ne 22/03/2018
Loan
Keywords: Interest; Annuities; Compound Interest